MEKANISME DAN PROSEDUR PENDIRIAN KOPERASI SYARIAH PERSPEKTIF ISLAM - Latifah, Yunita Shindi; Adjie Pambudi, Vito Pria; Sulistyowati, Sulistyowati (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2024)
This research aims to analyze the mechanisms and procedures for establishing sharia cooperatives from an Islamic perspective. The research method used is qualitative with a focus on literature studies as the main source. The data collection process involves searching and selecting relevant references from various information sources such as journal articles, digital libraries, and scientific publications. The collected data is then analyzed to identify relevant research findings and evaluate their suitability and relevance to the research objectives. The results of the discussion show that sharia cooperatives are economic entities that combine the principles of Islamic sharia with cooperative activities, with an emphasis on the prohibition of usury, the principles of justice, and the concept of togetherness. The procedure for establishing a sharia cooperative includes the formation of a management body, preparation of articles of association, formation of management, and official registration of the cooperative. From an Islamic perspective, sharia cooperatives play a role in realizing the values of justice, togetherness and social welfare in economic activities, as well as strengthening solidarity and collaboration in society. This research provides valuable insight into the mechanisms and procedures for establishing sharia cooperatives in accordance with Islamic principles.